Tannin as a renewable raw material for adhesive applications: a review. Issue 8 (6th April 2022) - Dhawale, Pritam V.; Vineeth, S. K.; Gadhave, Ravindra V.; Fatima M. J., Jabeen; Supekar, Mrudul Vijay; Thakur, Vijay Kumar; Raghavan, Prasanth
Abstract : Greener methods for the extraction and isolation of tannin, and it's state of art in adhesive technology. Abstract : Considering the limits of petrochemical availability and their toxicity, there has been rapid development and innovation in the field of alternatives for petrochemical adhesives. The carcinogenicity of formaldehyde has reduced the demand for formaldehyde-based wood adhesives, which has resulted in the development of adhesives based on renewable resources. This review article summarizes various works published on bio-derived adhesives focusing on tannin. Increasingly acknowledged renewability, sustainability, lower cost, and chemical modification opportunities make tannin a credible precursor for developing competent bio-based adhesives. Henceforth, the chemistry of tannin, its usefulness, possible chemical modification, and compatibility in an attempt to synthesize bio-based adhesives is also being highlighted and compared with its hydrocarbon-derived counterparts. In addition to this, categories of tannin, and techniques available for their extraction along with their pluses and misuses, have also been explained. Moreover, this review includes a detailed discussion on tannin as a raw material for preparing epoxy, polyurethane, polyethylenimine, and furfuryl-based adhesives. It is expected that by exploring further possibilities of chemical modification, tannin can be a potential candidate that can compete with the petrochemical-based adhesives, thereby paving the way for the advancement of bio-adhesives.